Elevated Levels of Pentraxin 3 Correlate With Neutrophilia and Coronary Artery Dilation During Acute Kawasaki Disease - Ching, Lauren L.; Nerurkar, Vivek R.; Lim, Eunjung; Shohet, Ralph V.; Melish, Marian E.; Bratincsak, Andras (Frontiers in Pediatrics, 2020)
Kawasaki disease (KD) is the leading cause of acquired pediatric heart disease in the developed world, as 25-30% of untreated patients and at least 5% of treated patients will develop irreversible coronary artery lesions (CAL). Pentraxin-3 (PTX-3) has been well studied in inflammatory diseases, in particular cardiovascular diseases associated with vascular endothelial dysfunction. We hypothesized that PTX-3 plays an important role in the development of KD associated CAL, and investigated circulating levels of PTX-3 in the serum of KD patients. Children with acute KD were followed from diagnosis through normalization of the clinical parameters of inflammation (convalescent phase). Serum samples were obtained and echocardiograms were conducted at several phases of the illness: acute (prior to intravenous immunoglobulin (IVIG) treatment), sub-acute (5-10 days after IVIG treatment) and convalescent (1-4 months after KD diagnosis). Seventy children were included in the final cohort of the study, 26 (37%) presented with CAL, and 18 (26%) developed IVIG resistance. Patients included in this study came from a diverse ethnic background. Significantly increased PTX-3 levels were observed during the acute phase of KD, compared to the sub-acute and convalescent phases. PTX-3 levels during acute KD were significantly higher among KD patients with CAL compared to patients with normal coronary arteries (NCA). Also, PTX-3 levels were significantly higher in patients with IVIG resistance. Further, PTX-3 levels were significantly higher in IVIG resistant KD patients with CAL as compared to the NCA group. Moreover, PTX-3 levels were significantly correlated to coronary artery z-score during acute KD and neutrophil counts throughout KD progression regardless of coronary artery z-score. Elevated PTX-3 levels correlated to elevated neutrophil counts, a known source of PTX-3 in acute inflammation, and an important player in the development of KD vasculitis. We, therefore, suggest PTX-3 as a novel factor in the development of KD associated CAL and propose neutrophil-derived PTX-3 as contributing to KD vascular dysfunction.